Making agriculture pro-nutrition: Opportunities in Tanzania - Ecker, Olivier; Mabiso, Athur; Kennedy, Adam; Diao, Xinshen (International Food Policy Research Institute, 2011)
Extreme poverty and chronic malnutrition are widespread in rural Tanzania, where smallholder agriculture dominates the economy. Given the sector's role as the main source of food and livelihood for many malnourished people, agriculture has substantial potential to reduce poverty and hunger. Unfortunately, to date, the agricultural sector has not yet reached this potential, and agricultural growth has not translated to significant improvements in nutrition outcomes at large. In this study, we explore the links between agriculture and nutrition in Tanzania and review the evidence on how these links can be strengthened for improved nutrition. We further quantitatively evaluate the potential nutrition outcome of agricultural growth through productivity-enhancing investments over the next five years.